2006
DOI: 10.1002/jor.20204
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ectopic bone growth induced by rhBMP‐2 on an absorbable collagen sponge in rat and rabbit models

Abstract: Recombinant human Bone Morphogenetic Protein-2 (rhBMP-2) is currently employed as an autograft replacement for spinal fusion. The morphogen is incorporated onto its carrier, an absorbable collagen sponge (ACS), in the operating room. Although the effectiveness of the rhBMP-2/ ACS implant in stimulating bone formation in human subjects has now been well established, further investigations of its use are necessary to deepen our understanding of its performance. The objective of the present study was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…Drugs with high molecular weight cannot easily permeate through skin. Sometimes adhesives may not adhere well to all types of skin and maybe uncomfortable to apply (Nishiyama et al, 1996;Hsu et al, 2006).…”
Section: Side Effects Of Bps Therapymentioning
confidence: 99%
“…Drugs with high molecular weight cannot easily permeate through skin. Sometimes adhesives may not adhere well to all types of skin and maybe uncomfortable to apply (Nishiyama et al, 1996;Hsu et al, 2006).…”
Section: Side Effects Of Bps Therapymentioning
confidence: 99%
“…The studies however have been performed in nude mice, from which it is known that cells are needed to stimulate bone formation. Other animal models such as rat, goat and rabbit are also inducible with an osteogenic material or growth factor 266 . For clinical translation, a cell-free construct would be ideal because harvesting, isolation and culturing of MSCs are time-consuming and costly.…”
Section: Contribution Of Seeded Mscs To Bone Formationmentioning
confidence: 99%
“…However, for the first time in 1988, these naturally occurring proteins were isolated and genetically reproduced to form recombinant human bone morphogenetic protein, or rhBMP. Like the naturally occurring protein, the recombinant form, according to several preclinical studies, has demonstrated the ability to induce new bone growth [16,18,19,20]. Specifically, rhBMP-2 has been studied more than any other BMP and has been approved by the Food and Drug Administration (FDA) for use in tibial, oral, and spinal surgical procedures.…”
Section: Should Surface Tads Be Considered?mentioning
confidence: 99%
“…Furthermore, studies have shown that when rhBMP-2 is used with a carrier, for example a collagen sponge, it has the ability to improve spinal fusion, increase periodontal new bone formation, and encourage fracture repair. In addition, rhBMP-2 has been used to regenerate defects of the mandible and skull, and help in the treatment of non-union, delayed union, and other skeletal conditions [13,15,18,19].…”
Section: Should Surface Tads Be Considered?mentioning
confidence: 99%